Analysis of threshed rice mixture separation through vibration screen using discrete element method - Hua, Li; Jinshuang, Wang; Jianbo, Yuan; Wenqing, Yin; Zhiming, Wang; Youzhang, Qian (International Journal of Agricultural and Biological Engineering, 2017)
The discrete element method was utilized to construct three-dimensional discrete element models for the rice mixture, and their motions were analyzed numerically on a planar vibration screening device. The results showed that, after falling onto the vibrating screen surface, the mixture undergoes a reciprocating motion within the same cycle. During the screening process, the mixture undergoes segregation, slides along the screen surface, passes through the screen and then falls. In comparing the movement of grains and shriveled grains, it can be seen that the velocity of shriveled grains experiences cyclical changes, which is consistent with the grains’ motion cycle. The impact on grains is shown to be greater than that on shriveled grains, and the average speeds of shriveled grains and grains converge. The curve shows that the screening of repetitive movements has a significant effect on the average velocity of shriveled grains, but also the velocity of shriveled grains and the vibration parameters can be well represented by a fitting equation. It is beneficial for the separation of grains from shriveled grains to choose a greater vibration frequency and screen surface inclination in the range of commonly used.Keywords: rice mixture separation, vibration screen, discrete element method, numerical computation, mechanismDOI: 10.25165/j.ijabe.20171006.2910Citation: Li H, Wang J S, Yuan J B, Yin W Q, Wang Z M, Qian Y Z. Analysis of threshed rice mixture separation through vibration screen using discrete element method. Int J Agric & Biol Eng, 2017; 10(6): 231–239.